The ENaQEnergy Signal Light: Collaboration and innovation forthe energy transition - Alcorta de Bronstein, Antonieta (2023)
In order to solve the grand societal challenges, achieve the Sustainable Development Goals (SDGs), or have a successful energy transition, innovations are essential. Furthermore, there is enough evidence that positively links innovation to sustainable development. However, an overview of the literature on the different understandings of innovation in relation to sustainable development shows that there is no agreement on a concept and many different conceptualizations (co)exist and are used at this intersection. In the transdisciplinary research project “ENaQ” the cornerstone is the development of innovations for an environmentally friendly neighborhood in Germany with a highly participatory approach. Hence, the concept of responsible research innovation in which all stakeholders are involved early on. The goal is to improve the possibilities of research and innovation benefiting society and preventing negative consequences. This goes in coherence with the ENaQ project, where participation is a fundamental element. However, other conceptualizations of innovation, for example, sustainability-driven, behavioral or social innovations, also apply, showing that some innovations will be a combination of these concepts. In this paper, we introduce one such innovation, the ENaQ Energy Signal Light. An innovation designed and developed within a participatory process with the aim to incentivize the use of green energy. A color light indicates when plenty of green energy is available, making it easier to visualize when is the best time to use energy-consuming household appliances such as a dishwasher or washing machine. In this paper, we will present the Energy Signal Light, and how it was developed within the ENaQ participation process. Furthermore, we have conducted a study to test the use and implications in behavior with three user groups, one using the Energy Signal Light itself, a second one using the digital version (in form of an App or website), and one control group. We will introduce preliminary results of the study.